2014
DOI: 10.1111/ajt.12763
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant IgG Reactivity to Apoptotic Cells Correlates With Late kidney Allograft Loss

Abstract: Pre-existing serum antibodies have long been associated with graft loss in transplant candidates. While most studies have focused on HLA-specific antibodies, the contribution of non-HLA-reactive antibodies has been largely overlooked. We have recently characterized monoclonal antibodies secreted by B cell clones derived from kidney allograft recipients with rejection that selectively bind to apoptotic cells. Here, we assessed the presence of such antibodies in pre-transplant serum from 300 kidney transplant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 47 publications
1
60
1
Order By: Relevance
“…These two subclasses are complement-fixing, pointing to a possible pathogenic role for these Nabs by complement-mediated graft damage. However, in contrast to our findings in renal transplant patients [10], we did not observe any association between pre-transplant IgG Nabs and rejection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These two subclasses are complement-fixing, pointing to a possible pathogenic role for these Nabs by complement-mediated graft damage. However, in contrast to our findings in renal transplant patients [10], we did not observe any association between pre-transplant IgG Nabs and rejection.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies we reported the implication of antibodies reactive to apoptotic cells in AMR following kidney transplantation [10]. These latter antibodies are known as natural antibodies (Nabs) as they are presumed to develop spontaneously in healthy individuals without the need for prior immunization [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study from our lab suggests otherwise. Using serum samples collected pre-transplant from 300 kidney transplant recipients, we found a significant correlation between the presence of polyreactive antibodies cross-reactive to apoptotic cells and late kidney graft loss 14 . Furthermore, the serum reactivity to apoptotic cells was almost exclusively attributable to IgG1 and IgG3, which displayed complement activation properties.…”
Section: Discussionmentioning
confidence: 93%
“…All serum specimens were collected prior to transplantation as part of the patients’ standard clinical care. The detailed characteristics of the patient population have been reported in a previous publication 14 . A succinct summary is provided in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast to kidney transplantation cohorts, where highly immunized patients are often observed (15). This low immunization grade can be explained by the fact that no retransplantation patients are present in our cohort.…”
Section: Discussionmentioning
confidence: 81%